Moderating Effect On The Relationship Between Internal Auditor And Audit Report Lag - Muhsin; Ayu Puspitasari (Jurnal Mantik, 2022)
The research sought to investigate and assess if firm size influences the relationship between internal auditors and audit report lag. The mining sector on the Indonesia Stock Exchange was subjected to quantitative research utilizing the variance-based Structural Equation Model analysis approach. According to the findings, the audit report lag in mining businesses ranged from 39 to 197 days. Internal auditor increased audit report lag, while firm size did not attenuate the relationship between internal auditor and audit report lag.